Angiostrongylus mackerrasae and A. cantonensis (Nematoda: Metastrongyloidea) belong to same genetic lineage: evidence from mitochondrial protein-coding genes - Song, Sze Looi; Yong, Hoi Sen; Eamsobhana, Praphathip (Cambridge University Press, 2018)
Angiostrongylus mackerrasae is a parasitic nematode of rats found in Australia. When first reported, it was referred to as A. cantonensis. Recent molecular studies, including the mitochondrial genome, indicate that it is highly similar to A. cantonensis. These studies did not include A. malaysiensis, another member of the A. cantonensis species complex, for comparison. The present study examined the genetic distance and phylogenetic relationship between the component taxa (A. cantonensis, A. mackerrasae and A. malaysiensis) of the A. cantonensis species complex, based on the 12 protein-coding genes (PCGs) of their mitochondrial genome. Both the nucleotide and amino acid sequences were analysed. Angiostrongylus mackerrasae and A. cantonensis are members of the same genetic lineage and both are genetically distinct from A. malaysiensis. The genetic distance based on concatenated nucleotide sequences of 12 mt-PCGs between A. mackerrasae and A. cantonensis from Thailand is p = 1.73%, while that between the Thai and Chinese taxa of A. cantonensis is p = 3.52%; the genetic distance between A. mackerrasae and A. cantonensis from China is p = 3.70%. The results indicate that A. mackerrasae and A. cantonensis belong to the same genetic lineage, and that A. mackerrasae may be conspecific with A. cantonensis. It remains to be resolved whether A. mackerrasae is conspecific with A. cantonensis or undergoing incipient speciation.